Governance in green construction: assessment of safety and health risks among the construction stakeholders - Muhamad Nabil, Zamani; Noor Akma, Abu Bakar; Fadzida, Ismail; Che Akmal, Che Yahaya; Fakhreldin, Mohammad (Universiti Malaysia Pahang Al-Sultan Abdullah Press, 2025)
Over the past few decades, researchers have paid a substantial amount of attention to green building design as well as its assessment. Moreover, the increasing emphasis on sustainable construction practices necessitates a comprehensive understanding of the associated safety and health risks (SHRs). Due to changes in materials, technologies, and construction procedures, green construction may increase safety and health hazards. This study aims to investigate the level of knowledge, attitudes, and practices regarding SHRs among the green construction stakeholders (including engineers, architects, contractors, sustainability consultants, suppliers, and developers). Additionally, this work intends to enhance the governance framework in green construction by proposing the integration of a simulation model to assess stakeholder knowledge, attitudes, and practices concerning SHRs among construction stakeholders in Kuala Lumpur, Malaysia. This study employed a survey method involving a comprehensive framework, with survey instrumentation, data collection and analysis methodologies, and a random sample size using G-Power of construction stakeholders in Kuala Lumpur, Malaysia. The findings revealed that stakeholders demonstrate a relatively high level of knowledge regarding green building design and assessment; their attitude towards green building practices is highly positive and consistent across stakeholders. Furthermore, stakeholders consistently practice green building design and assessment. Despite the progress in green construction methodologies, there is a notable gap in addressing the ethical and governance aspects related to safety and health. The proposed simulation model will facilitate the identification and mitigation of potential hazards early in the construction process, ensuring a safer working environment, which better predicts, manages, and responds to SHRs, thereby promoting a culture of safety and sustainability in the construction industry.